Unearthing Truth: Forensic Anthropology, Translocal Memory, and "Provention" in Guatemala - Mazzucelli, Colette G (2015)
This article deliberately examines the search for truth after decades of conflict in Guatemala. Excavations of mass gravesites and the painstaking exhumation processes carried out by professional forensic anthropology teams continue to allow families to locate lost relatives - reclaiming truth and supporting calls for justice. For Guatemalans, the search for truth now transcends national borders, especially among migrant communities in the United States. The family remains the central unit through which the work of Guatemalan forensic anthropologists is undertaken. In an effort to engender deeper insights about these exhumation processes from a social science perspective, this analysis promotes the use of specific "tools" in Guatemalan forensic anthropology investigations. The first is an exhumations concept map, which yields important questions meant to stimulate meaningful analysis. The second, Story Maps, is a technology application with the potential to mediate digital access t